Methods for detecting and developing protein-protein or protein-RNA interactions - Blakeley, Brett D., author; McNaughton, Brian, advisor; Kennan, Alan, committee member; Fisk, Nick, committee member; Reynolds, Melissa, committee member; Peersen, Olve, committee member (Colorado State University. Libraries, 2014)
Potent and selective recognition of disease-relevant macromolecules - such as proteins and RNA - is the molecular basis of most pharmaceuticals . Historically, small (< 500 Da) molecules have filled this role. However, the overwhelming majority (~85%) of the proteome - and emerging therapeutic targets such as RNA - present a serious challenge to small molecule-dependent recognition. An alternative approach to potent and selective recognition and regulation of disease-relevant proteins and RNA is to use synthetic proteins. In contrast to small molecules, the size, relatively high folding energies (>10 kcal/mol) and functional group diversity (by virtue of proteinaceous amino acids) allow proteins to recognize - and potentially control - macromolecular receptors that evade small molecules. Presented here are two approaches to advancing the discovery of new proteins that recognize either disease-relevant protein or RNA targets. The first part of this thesis describes split superpositive GFP reassembly as a method to identify novel protein-protein interacting pairs in living cells (E. coli). The second part of this thesis describes basic studies to evaluate the suitability of a naturally occurring RNA Recognition Motif (RRM) as a scaffold for targeting disease-relevant RNA hairpins, and the development of new RRMs that target TAR RNA, a hairpin critical to HIV proliferation.